Designing microcompression experiments for nanoporous metals via computational plasticity - Tim Fischer; Norbert Huber (Materials & Design)
Micropillar compression testing is essential for understanding bulk metal plasticity at small scales and has emerged as a key technique for evaluating nanoporous metals like nanoporous gold (NPG). To support experimental design, we present a computational plasticity study on single crystal NPG micropillars, systematically examining four extrinsic factors: pillar height-to-diameter ratio (1.5≤h/d≤2.5), taper angle (0≤θ≤4∘), friction coefficient (0.0≤μ≤0.2), and misalignment angle (0≤α≤2∘). The study reveals that NPG exhibits similar trends to its bulk counterpart but is less prone to post-yield buckling in unstable crystal orientations. For optimal NPG pillar stability, an aspect ratio of 1.5≤h/d≤2 is recommended and a moderate taper angle (θ≈2∘) to prevent artificial stiffening and yielding. Even minimal friction (μ≈0.05) enhances stability, while buckling is mainly governed by misalignment, requiring α≤1∘ to also avoid underestimating the elastic modulus.